If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 1 = 16 + 3x Reorder the terms: 1 + -8x = 16 + 3x Solving 1 + -8x = 16 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + -8x + -3x = 16 + 3x + -3x Combine like terms: -8x + -3x = -11x 1 + -11x = 16 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + -11x = 16 + 0 1 + -11x = 16 Add '-1' to each side of the equation. 1 + -1 + -11x = 16 + -1 Combine like terms: 1 + -1 = 0 0 + -11x = 16 + -1 -11x = 16 + -1 Combine like terms: 16 + -1 = 15 -11x = 15 Divide each side by '-11'. x = -1.363636364 Simplifying x = -1.363636364
| 5(2h-3)= | | b^11/b^4 | | x^2+2=224 | | y=0.50(1.06)50 | | 2(k+3)x-y=4 | | 2x^2+2=224 | | 3a^2b^3-24ab+18a= | | 2(z-9)=5(z+1)-11 | | 12x=535+4.50x | | 13.50x+15.50x=80 | | 4(x-3+4)=5(x-6+5) | | 13.50x+15.50y=1130 | | 0.66n+4=10 | | -1.5x=6.25 | | 80x=1130 | | 2y+6x+y+x+9+2x=2x+x+15-9 | | 4n-5=45 | | X/4=15/8 | | 5x+8=7x-3 | | 1-14x=12x+17 | | 14x-6y=18 | | R/98=-249 | | M/-31=13 | | -24=l/33 | | 15=k/-5 | | logx(66)=4 | | 9(2p-3)+6= | | 22+42=4(x-1)-4 | | 5=r/18 | | (2a+8)+(8+5a)= | | 17-62=79 | | 5/9=-5/6x-4/3 |